Invertebrate neurons as a simple model to study the hyperexcitable state of epileptic disorders in single cells, monosynaptic connections, and polysynaptic circuits - Brenes García, Oscar Gerardo (2022)
Epilepsy is a neurological disorder characterized by a hyperexcitable state in neurons from different brain regions. Much is unknown about epilepsy and seizures development, depicting a growing field of research. Animal models have provided important clues about the underlying mechanisms of seizure-generating neuronal circuits. Mammalian complexity still makes it difficult to define some principles of nervous system function, and non-mammalian models have played pivotal roles depending on the research question at hand. Mollusks and the Helix land snail have been used to study epileptic-like behavior in neurons. Neurons from these organisms confer advantages as single-cell identification, isolation, and culture, either as single cells or as physiological relevant monosynaptic or polysynaptic circuits, together with amenability to different protocols and treatments. This review’s purpose consists in presenting relevant papers in order to gain a better understanding of Helix neurons, their characteristics, uses, and capabilities for studying the fundamental mechanisms of epileptic disorders and their treatment, to facilitate their more expansive use in epilepsy research.